2006
DOI: 10.1152/ajpheart.00187.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective role of endogenous hydrogen peroxide during ischemia-reperfusion injury in canine coronary microcirculation in vivo

Abstract: We have recently demonstrated that endogenous H2O2 plays an important role in coronary autoregulation in vivo. However, the role of H2O2 during coronary ischemia-reperfusion (I/R) injury remains to be examined. In this study, we examined whether endogenous H2O2 also plays a protective role in coronary I/R injury in dogs in vivo. Canine subepicardial small coronary arteries (>or=100 microm) and arterioles (<100 microm) were continuously observed by an intravital microscope during coronary I/R (90/60 min) under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 39 publications
6
54
0
Order By: Relevance
“…However, the regulation of coronary vascular tone may be mediated, not only by NO, but also by the endothelium derived hyperpolarizing factor (EDHF) and adenosine (24). Yada et al have demonstrated that endogeneous H 2 O 2 , an EDHF, and rhokinase inhibition mediated coronary vasodilation to a greater extent in arterioles than in small arteries (7,8,24). In the present study, preservation of endotheliumdependent vasodilation by edaravone was noted to a greater extent in the small arteries (Fig.…”
Section: Edaravone Preserves Nitric Oxide and Enossupporting
confidence: 53%
See 2 more Smart Citations
“…However, the regulation of coronary vascular tone may be mediated, not only by NO, but also by the endothelium derived hyperpolarizing factor (EDHF) and adenosine (24). Yada et al have demonstrated that endogeneous H 2 O 2 , an EDHF, and rhokinase inhibition mediated coronary vasodilation to a greater extent in arterioles than in small arteries (7,8,24). In the present study, preservation of endotheliumdependent vasodilation by edaravone was noted to a greater extent in the small arteries (Fig.…”
Section: Edaravone Preserves Nitric Oxide and Enossupporting
confidence: 53%
“…4). Previous studies from our institution have also demonstrated a decrease in eNOS protein expression in ischemic myocardium following I / R (7,8). An in vitro study in HUVEC has shown that edaravone may increase eNOS expression via the inhibition of LDL oxidation (25).…”
Section: Edaravone Preserves Nitric Oxide and Enosmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, H 2 O 2 enhances the expression of both CD11b and CD18 on eosinophils (Nagata et al 2000). It has also been reported that H 2 O 2 plays an important role in cardioprotection against coronary I/R injury in vivo (Yada et al 2006). While this latter evidence supports an antiinflammatory role for H 2 O 2 , a greater body of evidence indicates a pro-inflammatory function for this molecule.…”
Section: Sex Differences In Leukocyte Recruitmentmentioning
confidence: 91%
“…12 Other investigators confirmed the importance of H 2 O 2 as an EDHF 13 in human 14 and canine 15,16 coronary microvessels and porcine pial arteries. 17 We also have demonstrated that endothelial nitric oxide synthase (eNOS) is a major source of EDHF/H 2 O 2 , 10 where copper, zincsuperoxide dismutase plays an important role to dismutate eNOS-derived superoxide anions to EDHF/H 2 O 2 18,19 and that endothelial NOSs system plays different roles depending on the vessel size, serving as the NO-generating system in large arteries and as the EDHF/H 2 O 2 -generating system in microvessels in mice.…”
Section: Editorial See P 12mentioning
confidence: 91%